Cultural Heritage And City Branding: The Role of Masjid Agung Kubah Timah in Pangkalpinang - Sri Rezeki, Nadia; Haprinda, Monica; Juhaini, Juhaini; Amin, Mat; Tuha, Panca Tuah; Aklil, Maulan (Academic Journal of Da'wa and Communication, 2024)
Bangka Island is famous as the largest tin producer in Indonesia. It has a distinctive history, culture, and religious diversity while upholding tolerance. However, the existence of tin on Bangka Island is not so felt as a symbol or characteristic in Pangkalpinang City as the Capital of the Province of Bangka Belitung Islands. Establishing the Great Mosque of the Tin Dome is currently the city branding of Pangkalpinang City. This study examines how the combination of resources, history, culture, and customs can become city branding. This research uses a descriptive qualitative method. Where the concentration of theoretical focus used is the development of a three-dimensional theoretical model that examines important elements in determining the elements, measurements, and equity of city branding. The data sources are obtained from interviews, secondary data, and also photographs of documentation. The results of the study show that the Great Mosque of the Tin Dome has met the requirements of city branding, namely 1) city brand elementshave met the history, process, graphics, and symbols; 2) city brand measurement is a process that starts from discussion, planning, narrative analysis, and visuals in its construction; and 3) city brand impact is very much felt by the identity, social and economic impact of the mosque's presence.